HUBUNGAN LITERASI DIGITAL DENGAN HASIL BELAJAR BAHASA INDONESIA PADA SISWA SEKOLAH DASAR - Rizki Aprilita; Septian Yolanda; Nikelia Safitri; M. Iqbal Arrosyad (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to describe and analyze the significant relationship between digital literacy and Indonesian language learning outcomes in elementary school students. Digital literacy is considered crucial in supporting Indonesian language learning, which now utilizes numerous digital sources and media. Improving digital literacy is expected to positively impact students' academic achievement, particularly in understanding, listening to, and creating Indonesian language content on digital platforms. This study used a quantitative method with a correlational approach. The subjects were students of SDN 38 Pangkalpinang, conducted on October 16, 2025. Data were collected using a questionnaire to measure digital literacy, based on four main indicators: internet search competency, hypertextual navigation, content evaluation, and knowledge organization. This data was then compared with students' Indonesian language learning outcomes. Based on the analysis, the overall level of digital literacy for students was in the Sufficient category with an average of 42%. This achievement indicates uneven mastery of digital competencies. However, the average Indonesian language learning outcome for students was in the Good category with a score of 71%.